Effect of process parameters on microstructural and mechanical properties of friction stir diffusion cladded ASTM A516-70 steel using 5052 Al alloy. (August 2018) - Ibrahim, Almigdad B.; Al-Badour, Fadi A.; Adesina, Akeem Yusuf; Merah, Nesar
Graphical abstract: Highlights: Friction Stir Diffusion Cladding (FSDC); a solid-state technique, was successfully employed to clad ASTM A516-70 steel with 5052-H32 aluminum alloy. Effect of tool rotation and traveling speeds on the quality of the clad system, interface microstructure, and mechanical properties were studied. Optimized parameters were determined. Tool advance per revolution was found to influence surface condition and clad integrity. Un-optimized process parameters resulted in formation of IMCs which affects the strength of the clad system. Abstract: In the present study, friction stir diffusion cladding (FSDC); a new solid-state process based on friction stir welding, was employed for cladding ASTM 516-70 steel with Al5052-H32 alloy. The effects of tool rotation and traveling speeds on microstructural and mechanical properties of the cladded system were investigated. Tool rotation speeds of 250, 500 and 1000 rpm and traveling speeds of 50, 100 and 150 mm/min were selected for evaluation at constant zero tilt angle and tool plunge depth of 2.0 mm. It is found that the combination of high rotational and high travel speeds results in lack of fill and voids on the cladded surface, while low rotational and high travel speeds result in weak bonding at the interface with disbandment of the cladding material. Similarly, surface roughness was found to increase with the tool advance per revolution (APR). Optimum properties were obtained at a combination of rotation/travel speeds of 500 rpm/50 mm/min. Specific fracture load of about 430 N/mm was found for samples with optimum process parameters.